Factors Predictive of Cerebral Hyperperfusion after Carotid Angioplasty and Stent Placement - Kaku, Yasuhiko; Yoshimura, Shin-ichi; Kokuzawa, Jouji (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Cerebral hyperperfusion syndrome has been increasingly reported as a complication of carotid angioplasty and stent placement. The aim of the present study was to determine significant predictors of hyperperfusion phenomenon after carotid angioplasty and stent placement.METHODS: We retrospectively reviewed 30 consecutive patients with unilateral severe carotid stenosis who underwent angioplasty and stent placement. Resting cerebral blood flow (CBF) and cerebral vasoreactivity (CVR) to acetazolamide challenge were quantitatively measured to evaluate cerebral hemodynamic reserve. Split-dose [123I] iodoamphetamine single photon emission CT (SPECT) was performed before and 7 days after carotid angioplasty and stent placement. Technetium-99m hexamethylpropyleneamine oxime (HMPAO) SPECT was performed immediately after the procedure.RESULTS: Three patients had cerebral hyperperfusion phenomenon immediately after angioplasty and stent placement, as shown by HMPAO SPECT: One developed status epilepticus 2 weeks after the procedure. Significant predictors of hyperperfusion included patient age, pretreatment CVR, and pretreatment asymmetry index ([ipsilateral resting CBF/contralateral resting CBF] × 100). Variables determined not to be significant risk factors included pretreatment resting CBF value, degree of carotid stenosis, and interval from the onset of ischemic symptoms.CONCLUSION: Significant predictors of hyperperfusion phenomenon after carotid angioplasty and stent placement included patient age, pretreatment CVR, and pretreatment asymmetry index. Pretreatment CBF measurements, including those obtained by quantifying CVR and performing SPECT immediately after the procedure may aid in identifying patients at risk and in initiating careful monitoring and control of blood pressure to prevent hyperperfusion syndrome.